The effectiveness of the implementation of a construction safety management system for the maturity safety culture in construction SOES - Bimo Prasetyo; Fatma Lestari (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
The construction industry is dangerous, with a high injury rate and death rate compared to other sectors. In the last decade, construction accidents in Indonesia have increased dramatically. H. W. Heinrich in his book The Accident Prevention reveals that 80% of work accidents are caused by unsafe actions and unsafe conditions. Construction safety is the safety of people who work (safe for people) in construction projects, and community safety (safe for the public). Therefore, the work safety system is a significant concern in suppressing the high number of work accidents in the construction industry. This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines. The scoping review framework was developed using PEO (Population, Exposure and Outcome). The population in question is construction workers in Indonesia, the exposure is Occupational Accident Safety, and the Outcome is the exposure and application of this work accident safety system which is the basis for researchers to determine keywords when conducting a literature Understanding hazard risks and implementing a good safety management system can change the safety culture in the company. Changes in safety culture that are getting better create a sense of security for workers and can increase work productivity. In the end, good business results will be obtained for the company. Keywords: individual characteristic; lactation support; lactation facilities; working mother; workplace